Karakterisasi Arang Magnetik Dari Cangkang Kelapa Sawit Dalam Mereduksi Asam Lemak Bebas (ALB) Minyak Jelantah - Efrizal Siregar; Khairil Anwar (ABEC Indonesia, 2022)
Used cooking oil is the final product of oil used for frying or cooking in the manufacturing, restaurant and household industries which is often not utilized. Most users will throw the used cooking oil waste into inappropriate places such as in the kitchen, sink or so on, the used cooking oil can harden and clog the sewer pipe. This can also result in the formation of a thin layer on the surface of the water which can reduce the concentration of dissolved oxygen needed by living things underwater. To reduce the impact of waste cooking oil that will occur in the water system, this study intends to develop magnetic charcoal from palm oil shells to process used cooking oil waste into a pretreatment for biodiesel production. Biodiesel is a promising alternative fuel as a substitute for fossil fuels that are decreasing. The purpose of this study was to utilize magnetic charcoal from palm oil shells to reduce free fatty acids from waste cooking oil as a pretreatment for biodiesel production. The method used is pyrolysis and coprecipitation with the formation of magnetic charcoal from oil palm shells with the precipitation process with FeCl3 (iron III chloride) and FeSO4 (iron II sulfate). then tested the characteristics of the magnetic charcoal that had been produced using Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscope (SEM). Next is to test the absorption of free fatty acid reduction from used cooking oil using magnetic charcoal that has been produced by varying the time, concentration and dose of magnetic charcoal to get the maximum adsorption capacity. Then do adsorption 3 times to evaluate the efficiency of reduction of free fatty acids in used cooking oil as a pretreatment for biodiesel production